2011
DOI: 10.1111/j.1741-1130.2011.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

Adults With Intellectual Disabilities Living in Hong Kong's Residential Care Facilities: A Descriptive Analysis of Health and Disease Patterns by Sex, Age, and Presence of Down Syndrome

Abstract: The aim of this study was to describe the health status profile and identify the healthcare needs of adults with intellectual disability (ID) residing in 18 of Hong Kong's residential care facilities. The author employed a cross‐sectional study using a structured questionnaire survey to collect data on 811 persons with ID (432 males, 53.3%, and 379 females, 46.7%) with an average age of 44. Of the residents, 107 (13.2%) had Down syndrome, 275 (34%) had epilepsy, and 134 (16.6%) had cerebral palsy. Some 25.4% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 8 publications
0
23
1
Order By: Relevance
“…Assessment of prevalence in the included studies was made using a range of methods, including data extraction from medical records [32][33][34][35][36], survey [26,[37][38][39][40], interview [41], and physical examination [21,42,43]. The largest study comprised 27 116 participants [37], while the smallest comprised four participants [17].…”
Section: Study Characteristics and Quality Appraisalmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of prevalence in the included studies was made using a range of methods, including data extraction from medical records [32][33][34][35][36], survey [26,[37][38][39][40], interview [41], and physical examination [21,42,43]. The largest study comprised 27 116 participants [37], while the smallest comprised four participants [17].…”
Section: Study Characteristics and Quality Appraisalmentioning
confidence: 99%
“…The average age of participants was 46 years (excluding three studies in which age was not reported); the youngest mean age was 35.4 years [21] and oldest 61.5 years [32]. Six studies were conducted in the USA [21,[33][34][35][36][37]43], three in the Netherlands [32,41,44], and one each in Hong Kong [38], China [42], Europe [39] and the UK [40]. Seven studies reported obtaining ethics clearance [21,32,33,36,38,41,43].…”
Section: Study Characteristics and Quality Appraisalmentioning
confidence: 99%
“…Clinical convenience samples ascertained through specialty clinics focused on DS or intellectual and developmental disabilities (IDD) have also been used to estimate the prevalence and variety of medical conditions in adulthood (Henderson, Lynch, Wilkinson, & Hunter, ; Jensen, Taylor, & Davis, ; Jones, ; Real de Asua, Quero, Moldenhauer, & Suarez, ; van Allen et al, ; Van Buggenhout et al, ). Occasionally IDD population‐based databases have been utilized to compile this information using survey methods (Maatta et al, ; Wong, ).…”
Section: Introductionmentioning
confidence: 99%
“…Primarily, the included studies were cross-sectional observational (n = 31 81,82,98,[100][101][102]104,106,[109][110][111]114,116,119,121,124,[126][127][128][129][130][131][132][133][134][135]137,139,142,143,145 ). The remaining studies involved retrospective database or medical records data (n = 22 [83][84][85][86][87][88][89]94,95,99,107,113,115,117,118,120,122,123,136,…”
Section: Study Characteristicsmentioning
confidence: 99%